VIEWING THE PRACTICE OF TODAY'S CHRISTIAN POLITICS: POST PRESIDENTIAL ELECTION REFLECTION - Togardo Siburian (Societas Dei: Jurnal Agama dan Masyarakat, 2019)
This paper wants to rethink the political attitudes and views of the churches at the time of the last democratic party. the aims also to reflect them broadly and enrich their discussion with the study of literature. There are practical political concerns carried out by the churches as institutions that consciously and systematically become partisans, as well as the ambivalence in the attitude of the leaders of the local churches when facing the five-year presidential election. By actively campaigning for covertness in the middle of the church even on the pulpit of the church. There is a dilemma in the behavior of church members about the relationship between faith and politics, there is less undestandeing of the apolitical attitude of the church that separates religion and the State. The unity of political movements in the "false" coalition to win certain candidates of presidential election contestation.